Kondisi Sanitasi Terminal Mabu’un Kabupaten Tabalong - Tien Zubaidah; Rusinta Rusinta (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2015)
Abstract: Sanitary Conditions Terminal Mabu'un Tabalong. One impact of the terminal is the possibility of disease transfer and transmission of vector -borne diseases through the means of conveyance . This study aims to determine the sanitary conditions in the Terminal Mabu'un Tabalong . Data were collected in the form of frequency tabulation then analyzed descriptively and compared with the requirements according to DEPKES DITJEN . PPM and PLP 1999. The result show that the sanitation in Terminal Mabu'un Tabalong including healthy feasible for terminal infrastructure with a yield of 86.0 percent of ≤ 75 percent of the specified conditions. However there are several aspects that need attention sanitation ie from outside environmental health aspects, sanitation space and buildings , sanitary facilities and food sanitation . Efforts are being made to improve sanitation in Terminal Mabu'un Tabalong like doing cleaning around the terminal, power supply cleaning service for the reception area , increasing the number of bins, sanitary inspection terminals and provide counseling . Keywords : Health environment, sanitation value , sanitation terminal